Cerebrospinal Fluid ACTH and Cortisol in Opsoclonus-Myoclonus: Effect of Therapy - Pranzatelli, Michael R.; Chun, Kelly Y.; Moxness, Michael; Tate, Elizabeth D.; Allison, Tyler J. (Pediatric neurology, 2005)
Opsoclonus-myoclonus syndrome is one of a few corticotropin (ACTH)-responsive central nervous system disorders of childhood. We measured cerebrospinal fluid ACTH and cortisol in 69 children with opsoclonus-myoclonus and 25 age- and sex-matched control subjects to determine endogenous levels and look for hypothesized differential hormonal effects of ACTH and corticosteroid treatment. Cerebrospinal fluid cortisol was 10-fold higher with ACTH treatment (n = 26), but was unchanged with oral steroid treatment (n = 18) or no treatment (n = 25). It was significantly higher in children receiving daily high-dose ACTH than alternate day ACTH. In ACTH-treated children, cerebrospinal fluid and serum cortisol were highly correlated ( r = 0.96, P = 0.0001), with a mean ratio of cerebrospinal fluid to serum cortisol of approximately 1:10. Cerebrospinal fluid ACTH concentration did not differ significantly between untreated opsoclonus-myoclonus and control subjects but was lower with ACTH (−29%) or steroid treatment (−36%), suggesting feedback inhibition of ACTH release. These data delineate differences in the central effects of ACTH and corticosteroid therapy, as well as between high and low ACTH doses, and support the integrity of the brain-adrenal axis in pediatric opsoclonus-myoclonus.